2011
DOI: 10.1007/s00415-011-5914-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism in DM1 and its relationship to erectile dysfunction

Abstract: Myotonic dystrophy type 1 (DM1) is characterized by both a premature appearance of age-related phenotypes and multiple organ involvement, which affects skeletal and smooth muscle as well as the eye, heart, central nervous system, and endocrine system. Although erectile dysfunction (ED) is a frequent complaint in patients with DM1, it has not been investigated in great depth. Hypogonadism, which is reported to be one of the physical causes of ED in the general population, frequently occurs in DM1. We planned th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Antonini et al . investigated hypogonadism and erectile function in 30 men with DM1 and found hypogonadism in 60%. Almost 90% of the hypogonadal men had erectile dysfunction compared with 42% of those who were eugonadic.…”
Section: Discussionmentioning
confidence: 99%
“…Antonini et al . investigated hypogonadism and erectile function in 30 men with DM1 and found hypogonadism in 60%. Almost 90% of the hypogonadal men had erectile dysfunction compared with 42% of those who were eugonadic.…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine abnormities have been reported in MD2 and MD1 patients (Figure 4), including the alteration in testicular function such as hypogonadism leading to oligospermia [91], low levels of testosterone (T), and reduced spermatogenesis [92], resulting in reduced male fertility. In fact, hypogonadism may be a cause for erectile dysfunction (ED), which has been demonstrated in 25% of patients with MD1 [93].…”
Section: Adult Muscular Dystrophiesmentioning
confidence: 99%
“…Testicles of MD1 patients are characterized by an increase in the number and size of Leydig cells as well as tubular atrophy, hyalinization, fibrosis of the seminiferous tubules and reduced spermatogenesis. It has been reported that 46% of MD1 patients show hormonal evidence of interstitial gonadal failure [97, 99]. …”
Section: Adult Muscular Dystrophiesmentioning
confidence: 99%
“…DM1 is a multi-systemic disorder affecting skeletal muscle, with myotonia and prominent muscle weakness and atrophy, as well as eye, heart, endocrine, and central nervous systems. Abnormal levels of steroid hormones, such as testosterone and DHEA have been reported in DM1 [1][2][3]. Moreover, recent studies showed that in DM1 patients there is an increased risk of calcium metabolism disorders such as hyperparathyroidism that seem to correlate with CTG expansion size [1].…”
Section: Introductionmentioning
confidence: 99%